HAZOP Study and SIL Verification of Fuel Gas System in ORF Using IEC 61511 Standard and FTA Method - Nurhadi Siswantoro; Dwi Priyanta; Afanda Dwi Ragil Risnavian; M. Badrus Zaman; Trika Pitana; Hari Prastowo; Semin Semin (International Journal of Marine Engineering Innovation and Research, 2022)
Safety is an important aspect of the industrial process. Failure of system and mechanism endanger both human and environmental safety. Safety is obligated to be implemented precisely and thoroughly to prevent failure consequences. One of the preventive implementations is to map out safety devices in the form of SIS (Safety Instrumented System) and other layers of protection. However, to acknowledge this safety device performance used SIL (Safety Integrity Level). This final research is intended to analyze Fuel Gas systems on Onshore Receiving Facilities (ORF). HAZOP (Hazard Operability Study) as process hazard analysis with deviation during the operation so that the risk level is known. SIL verification towards SIL target is SIL-2 refer to IEC 61511 standards by FTA (Fault Tree Analysis) method. From the HAZOP study can be concluded that over-pressure becomes a top hazard to all nodes due to the most severe consequences, the highest likelihood (medium risk). The calculation result of PFDavg is Node 1 (Fuel Gas Scrubber V-6060) is 6,22E-03, Node 2 (Fuel Gas Filter Separator S-6060A) is 1,24E-03, Node 3 (Fuel Gas Filter Separator S-6060B) is 1,24E-03, Node 4 (Fuel Gas Superheater E-6060) is 1,21E-03, and Node 5 (Instrument Gas Receiver V-6070) is 2,23E-03. The conclusion of this research shows that five components of the Fuel Gas System fulfill the SIL-2 target, therefore, doing a re-design to add a safety device is unnecessary